Wound process influence on formation systemic inflammatory response and early sepsis in patients with burns in acute period of burn disease - Kozinets, G. P.; Оsadcha, О. І.; Kovalenko, O. M.; Lynnyk, O. M. (Modern medical technology, 2019)
Purpose of the study. Determine the mechanism of influence of the wound process on the formation of early sepsis in patients with burns in the acute period of burn disease. Materials and methods. The results of the examination and treatment of 43 patients aged 16–58 years with the area of burn injury from 20% to 60% of the body surface are analyzed. Patients underwent research in the capillary zone of thermal damage to the contents of homocysteine, endothelin and nitric oxide, and the level of cytokines in the blood. Results. Ischemia in the first day after injury and subsequent reperfusion increase in the linear blood flow speed is an incentive for increased production of nitric oxide, which promotes vasodilatation and impaired tissue perfusion, the formation of ischemic centers in the burn wound and the activation of cells that produce cytokines and other inflammatory mediators. The dynamics of changes in the activity of NG (neutrophil granulocytes) in spontaneous NST-test (nitro blue tetrazolium test) indicates a high degree of functional damage of phagocytic cells. The decrease in the indexes of myeloperoxidase and PAS-positive substancesinneutrophilgranulocytesisaconfirmation of enzymatic and energetic activity degradation. When activating Mf-residents (resident macrophages) in response to injury, cells with low functional efficiency migrate to the zone of thermal damage. The increase in the content of proinflammatory cytokines with a significant reduction of antiinflammatory agents is found out, which leads to dysregulation of cytokine interactions. Significant secretion of IL-6 activates the cascade synthesis of proinflammatory cytokines IL-1, IL-2 and TNF in the absence of adequate inhibition by antiinflammatory mediators leads to the generalization of systemic inflammatory response. Conclusions. It was determined that the predictors of early sepsis in patients with severe burns are: progressive decrease in the content nitric oxide degradation products with a significant increase of homocysteine and endothelin-1 content; progressive increase IL-6 level, which activates the cascade synthesis of proinflammatory cytokines (IL-1, IL-2, TNF-а); increase in the activity of resident macrophages and suppression of functional activity of inflammatory macrophages in relation to microbial agents; progressive myeloperoxidase decrease in neutrophil granulocytes in the capillary blood of thermal injury zone in the early stages after burn trauma.